Penggunaan Metode Problem Solving Dengan Gallery Walk Pada Materi Masa Pendudukan Jepang Di Indonesia Untuk Meningkatkan Hasil Belajar - Sri Fatmawati (Pendidikan IPS FKIP ULM, 2023)
Teachers have various techniques at their disposal to improve students' learning effectively. Of all the learning methods, problem-solving is a potent means to enhance students' understanding. However, it remains challenging for educators to select the appropriate method for students and align it with the academic curriculum. The primary objective of this study was to analyse the effectiveness of the problem-solving method, media gallery walk, in improving student learning outcomes on the topic of Japanese occupation in Indonesia. The research was conducted on class XI MIPA2 students at SMA Negeri 10 Banjarmasin using the classroom action research methodology. The study encompassed 35 students as its participants, and the data collected included teacher and student activity data gathered through observation and student learning outcomes data acquired from tests. The research findings indicated that the teacher's activity score increased from 12 in a meeting I to 19 in meeting IV. Similarly, the student activity percentage rose from 37% in meeting I to 100% in meeting IV, meeting II recorded a 51% activity score, and meeting III obtained an 88% score. In conclusion, using the problem-solving method, media gallery walk, can substantially increase teacher and student engagement and enhance the overall student learning outcomes for class XI MIPA2 students at SMA Negeri 10 Banjarmasin.Keywords: Student activity, learning outcomes, problem-solving, gallery walk.